ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP PEMEGANG SAHAM MINORITAS DALAM PERUSAHAAN TERBUKA - Wina Wina; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2018)
ABSTRACT Legal protection for minority shareholders in a public company is being so crucial because their interest is related to public interest. Moreover, the minority shareholders are always prone to be exploited by majority shareholders or Directors and Commissioners of the company, and they can do anything which harms minority shareholders. Besides that, weak protection for minority shareholders can have the impact on the development of capital market industry so that protection for them should be accommodated. This thesis discusses the problem of legal principles for the protection of minority shareholders in a public company, the norm of protection for minority shareholders in a public company on capital market field legislation, and inefficiencies in the protection.   Keywords : Legal Protection, Minority Shareholders, Public Company